The role of climate and population change in global flood exposure and vulnerability - Justin S. Rogers; Marco M. Maneta; Stephan R. Sain; Luke E. Madaus; Joshua P. Hacker (Nature Communications)
Abstract Flooding is a pervasive natural hazard with wide-ranging impacts on society. Using a high-resolution global flood model considering coastal, fluvial, and pluvial hazards, we clarify the role of climate effects versus population growth effects in changing flood exposure. Between 2020 and 2100, the population likely exposed to 1% annual risk (100-year) flood hazard will increase from 1.6 to 1.9 billion people. Of this change from the 2020 exposure, we attribute 21.1% to climate change, 76.8% to population change, and 2.1% to both climate and population change. The largest driver of uncertainty in exposure is population change, while climate change remains a smaller but still important driver. The global increase in exposure between 2020 and 2100 is primarily driven by low-GDP regions, and by 2100 the lowest GDP areas will make up 63% of the exposure both overall and in urban areas. Urban areas are especially vulnerable in nearly all global regions, and urban areas sensitive to extreme events are expected to see a 33% increase in population exposure. This study highlights the vast inequities in flood exposure, and future work should direct resources and strategies toward sustainable risk mitigation in these areas.